Assessment of Myocardial Function During Blood Pressure Manipulations Using Feature Tracking Cardiovascular Magnetic Resonance - Fischer, Kady; Neuenschwander, Mario D.; Jung, Christof; Hurni, Samuel; Winkler, Bernhard M.; Huettenmoser, Stefan P.; Jung, Bernd; Vogt, Andreas P.; Eberle, Balthasar; Guensch, Dominik P. (Frontiers in Cardiovascular Medicine, 2021)
Background: Coronary autoregulation is a feedback system, which maintains near-constant myocardial blood flow over a range of mean arterial pressure (MAP). Yet in emergency or perioperative situations, hypotensive or hypertensive episodes may quickly arise. It is not yet established how rapid blood pressure changes outside of the autoregulation zone (ARZ) impact left (LV) and right ventricular (RV) function. Using cardiovascular magnetic resonance (CMR) imaging, measurements of myocardial tissue oxygenation and ventricular systolic and diastolic function can comprehensively assess the heart throughout a range of changing blood pressures. Design and Methods: In ten anesthetized swine, MAP was varied in steps of 10-15 mmHg from 29-196mmHg using phenylephrine and urapidil inside a 3-Tesla MRI scanner. At each MAP level, oxygenation-sensitive (OS) cine images along with arterial and coronary sinus blood gas samples were obtained and blood flow was measured from a surgically implanted flow probe on the left anterior descending coronary artery. Using CMR feature tracking-software, LV and RV circumferential systolic and diastolic strain parameters were measured from the myocardial oxygenation cines. Results: LV and RV peak strain are compromised both below the lower limit (LV: Δ1.2±0.4%, RV: Δ4.4±1.2%, p<0.001) and above the upper limit (LV: Δ2.1±0.4, RV: Δ5.4±1.4, p<0.001) of the ARZ in comparison to a baseline of 70mmHg. LV strain demonstrates a non-linear relationship with invasive and non-invasive measures of oxygenation. Specifically for the LV at hypotensive levels below the ARZ, systolic dysfunction is related to myocardial deoxygenation (β=-0.216, p=0.036) in OS-CMR and both systolic and diastolic dysfunction are linked to reduced coronary blood flow (peak strain: β=-0.028, p=0.047, early diastolic strain rate: β=0.026, p=0.002). These relationships were not observed at hypertensive levels. Conclusion: In an animal model, biventricular function is compromised outside the coronary autoregulatory zone. Dysfunction at pressures below the lower limit is likely caused by insufficient blood flow and tissue deoxygenation. Conversely, hypertension-induced systolic and diastolic dysfunction points to high afterload as a cause. These findings from an experimental model are translatable to the clinical peri-operative environment in which myocardial deformation may have the potential to guide blood pressure management, in particular at varying individual autoregulation thresholds.